An update on inflammatory markers in metabolic syndrome - Giri, Akshay Prashanth; Shanmugam, Lokesh (International Journal of Advances in Medicine, 2021)
Metabolic syndrome is an emerging global threat as a major health burden. It is widely presumed that Metabolic syndrome is associated with a low grade chronic inflammatory phenomenon. This inflammatory state is due to the imbalance between the pro and anti-inflammatory cytokines. Studies have been performed on various inflammatory markers in metabolic syndrome like hsCRP, TNF-alpha, Adiponectin, IL-6, IL-10. Articles were chosen from indexed journals from various search engines. Pro inflammatory cytokines like hsCRP, TNF – alpha, Interleukin -6 were found to be increased and anti-inflammatory cytokines like Interleukin – 10 were reduced in metabolic syndrome.